Revision of Megabeleses Takeuchi (Hymenoptera, Tenthredinidae) with description of two new species from China - Wei, Meicai (Zootaxa, 2010)
Megabeleses Takeuchi, 1952 is redescribed and a key to species provided. Megabeleses magnoliae, sp. nov. and M. xiaoi, sp. nov. from China are described. M. liriodendrovorax Xiao, 1993, M. crassitarsis Takeuchi, 1952 and M. tsurugiensis Togashi, 2008 are redescribed and illustrated based on types and new material.